“Does the doctor think I’m Crazy?”: Stories of low-income Cape Town women receiving a diagnosis of somatic symptom disorder and their subsequent referral to psychological services - Cowlin, Avril Moira (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015